Intestinal Barrier Integrity in Heat-Stressed Modern Broilers and Their Ancestor Wild Jungle Fowl - Tabler, Travis W.; Greene, Elizabeth S.; Orlowski, Sara K.; Hiltz, Joseph Z.; Anthony, Nicholas B.; Dridi, Sami (Frontiers in Veterinary Science, 2020)
High environmental temperature has strong adverse effects on poultry production, welfare, and sustainability and, thereby, constitutes one of the most challenging stressors. Although colossal information has been published on the effects of heat stress on poultry productivity and gut health, the fundamemntal mechanisms associated with heat stress responses and intestinal barrier function are still not well defined. The aim of the present study was, therefore, to determine the effects of acute (2h) heat stress on growth performance, gut integrity, and intestinal expression of heat shock and tight junction proteins in slow- (broilers of the 1950’s, ACRB), moderate- (broilers of 1990’s, 95RAN), rapid-(modern broilers, MRB) growing birds, and their ancestor wild jungle fowl (JF). Heat stress exposure significantly increased the core body temperature of 95RAN and MRB chickens by approximately 0.5-1°C, but not that of JF and ACRB compared to their counterparts maintained at thermoneutral conditions. Heat stress also depressed feed intake and increased serum FITC-D levels (P<0.05) in modern broilers (95RAN and MRB) but not in JF and ACRB, indicating potential leaky gut syndrome. Molecular analyses showed that heat stress exposure significantly up regulated the duodenal expression of OCLN and LCN2 in ACRB, ZO-2, VIL1, and CALPR in 95 RAN, and only CALPR in MRB compared to their TN counterparts. In the jejunum however, HS down regulated the expression of PATJ in ACRB, 95RAN, and MRB, and that of CDH1 in MRB. In the ileum, HS significantly down regulated the expression of OCLN in 95 RAN, ZO-1 in MRB, GJA1 in JF, and VIL1 in ACRB compared to their TN counterparts. In summary, this is the first report, to our knowledge, showing that tight junction protein expression is environmental-, genotype-, and intestinal segment-dependent and identifying molecular signatures, such as CDH1, CALPR and ZO-1, potentially involved in leaky gut syndrome-iduced by heat stress in MRB.